1999
DOI: 10.1046/j.1468-2982.1999.1909797.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine-Related Seizures in an Epileptic Population

Abstract: A relationship between epilepsy and migraine has long been postulated, but the nature of this interaction is still debated. We studied adult patients with epilepsy and investigated the relationship between migraine and epilepsy. Fourteen percent (n = 412) of adult patients with seizures were identified with a diagnosis of migraine. We also found a direct relationship between migraine and epilepsy (a migraine-induced epilepsy) in 1.7% (seven patients) of the patients with seizures. Patients were at increased ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 13 publications
1
46
1
3
Order By: Relevance
“…In our study, five patients had preictal headaches with migrainous qualities, albeit only four with sufficient duration (>4 h) to be classified as migraine. None experienced migraine auras, in contrast to other studies [19,20].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In our study, five patients had preictal headaches with migrainous qualities, albeit only four with sufficient duration (>4 h) to be classified as migraine. None experienced migraine auras, in contrast to other studies [19,20].…”
Section: Discussioncontrasting
confidence: 83%
“…Many authors have tried to explore this association, but with rather diverse findings. The prevalence of migraine in individuals with epilepsy varies from 2% to 24% [4,6,7,11,12,[16][17][18][19][20]. This large variation is probably due to differences in classifications of both disorders, as well as in the selection of patient populations and diagnostic instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Seizures as a trigger in patients genetically prone to migraine should be taken into account like other potent triggers (e.g., nitroglycerin) to a susceptible brain. The data concerning migraine aura induced epilepsy (migralepsy) is highly variable and was reported in 1.7-16 % of patients suffering from epilepsy and migraine with aura [59,105]. Comorbidity of migraine and epilepsy leads to negative effect on the prognosis of epilepsy with lower probability of being seizure free after a 10-year followup and a higher incidence of intractable epilepsy [104].…”
Section: Migraine and Epilepsymentioning
confidence: 99%
“…A relationship between migraine and epilepsy has long been postulated, with recent clinical and epidemiological studies having demonstrated that both are highly co-morbid [83][84][85]. Although migraine prevalence in patients with epilepsy is high (14% to 20%), only a few (1.7% to 3%) experience seizures in close temporal proximity to migraine [84,85].…”
Section: Risk Factors In Migraine Headachementioning
confidence: 99%
“…Although migraine prevalence in patients with epilepsy is high (14% to 20%), only a few (1.7% to 3%) experience seizures in close temporal proximity to migraine [84,85].…”
Section: Risk Factors In Migraine Headachementioning
confidence: 99%